1997
DOI: 10.1097/00000658-199710000-00016
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized Trial of Early Enteral Feeding After Resection of Upper Gastrointestinal Malignancy

Abstract: ObjectiveThe purpose of the study was to determine whether early postoperative enteral feeding with an immune-enhancing formula (IEF) decreases morbidity, mortality, and length of hospital stay in patients with upper gastrointestinal (GI) cancer. Summary Background DataEarly enteral feeding with an IEF has been associated with improved outcome in trauma and critical care patients. Evaluable data documenting reduced complications after major upper GI surgery for malignancy with early enteral feeding are limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
179
1
6

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 346 publications
(198 citation statements)
references
References 24 publications
5
179
1
6
Order By: Relevance
“…For this reason, in the previous studies on early enteral nutrition after esophagogastric surgery, enteral nutrition was often administered via an intestinal tube (naso-jejunal tube or catheter jejunostomy) to protect anastomosis [19][20][21][22]. However, several experimental and clinical studies have demonstrated that early enteral feeding increases wound healing and anastomotic strength in intestines and somatic tissues [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, in the previous studies on early enteral nutrition after esophagogastric surgery, enteral nutrition was often administered via an intestinal tube (naso-jejunal tube or catheter jejunostomy) to protect anastomosis [19][20][21][22]. However, several experimental and clinical studies have demonstrated that early enteral feeding increases wound healing and anastomotic strength in intestines and somatic tissues [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Biologically, there have been several reasons reported including better substrate utilization, prevention of mucosal atrophy, preservation of normal gut flora, gut integrity, and immune competence. Early enteral vs parenteral feeding in traumatized and surgical patients is gaining wide consensus after the promising results showing good tolerance and notable reduction of septic morbidity [1,[6][7][8][9] . Our data confirm that early postoprative enteral feeding may be carried out safely in patients who have undergone major operations for cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most clinical studies did not compare enteral nutrition and total parenteral nutrition in a randomized fashion [14,22,24]. Of the studies performed in a prospective randomized fashion [9,25,26], the patients studied were not limited to esophageal cancer patients, such that the bona fide effects of EEN in esophageal surgery were not clear. Furthermore, the term Bearly^was defined as EN started within 24-48 h after admission or surgery [27]; however, EN started within 24 h had shown no advantage for the postoperative course in esophageal cancer [28].…”
Section: Discussionmentioning
confidence: 99%